Healthcare Provider Perspectives on Lowering Colorectal Cancer Screening Initiation Age to 45 Years: Results From a Survey of Clinicians in the U.S. (17th December 2020) - Rutten, Lila J. Finney; Parks, Philip; Weiser, Emily; Zhu, Xuan; Griffin, Joan M.; Limburg, Paul J.
We conducted a survey of primary care clinicians and gastroenterologists (n = 938) between 11/06/19–12/06/19 to assess knowledge and attitudes regarding colorectal cancer screening. We assessed clinicians' attitudes toward lowering the colorectal cancer screening initiation age to 45 years, a topic of current debate. We also evaluated provider and practice characteristics associated with agreement. Only 38.1% of primary care clinicians endorsed colorectal cancer screening initiation at age 45 years, compared to 75.5% of gastroenterologists (p < .0001). Gastroenterologists were over 5 times more likely than primary care clinicians to endorse lowering the screening initiation age (OR = 5.30, 3.54-7.93). Other factors found to be independently associated with agreement with colorectal cancer screening initiation at age 45 years included seeing more than 25 patients per day (vs. fewer) and suburban (vs. urban) location. Results emphasize the need for collaboration between primary care clinicians and gastroenterologists to ensure that patients receive consistent messaging and evidence-based care.